Assessment of awareness of common rheumatological diseases amongst final year medical undergraduate students: single centre questionnaire-based survey - Thomas, Elizabeth Mary; Surendran, Sandeep; Marwaha, Vishal; Tiwari, Arun; Movva, Hamsini; Lalwani, Chiraj (International Journal of Research in Medical Sciences, 2020)
Background: Assessment of awareness of common rheumatological diseases amongst final year medical undergraduate students – single centre questionnaire-based survey. Methods: A cross-sectional survey of final year students was conducted during a national undergraduate medical summit. Participants were asked to fill out a 10-question survey (online link/in print). Results were summarized using descriptive statistics. Results: A total 162 medical students completed the survey. Only 18 of 162 respondents were able to score more than 50% in all domains with only one respondent getting all the questions correct. Partial awareness about the major rheumatological diseases in adults was seen with 122 (75%), 110 (68%) and 105 (65%) students having more than 50% correct in the domains of lupus, psoriasis and rheumatoid respectively without scoring completely. By contrast even general awareness of pediatric rheumatology was low with only 34 respondents (21%) having more 50% score in this domain. Conclusions: These findings are consistent with the general consensus amongst rheumatologists that medical students are inadequately exposed to rheumatological disorders and evolving treatments. Awareness of paediatric rheumatology is the lowest and needs urgent addressing.